Implementing Community Based Primary Healthcare for Older Adults with Complex Needs in Quebec, Ontario and New-Zealand: Describing Nine Cases - Breton, Mylaine (Int J Integr Care, 2017)
The aim of this paper is to set the foundation for subsequent empirical studies of the “Implementing models of primary care for older adults with complex needs” project, by introducing and presenting a brief descriptive comparison of the nine case studies in Quebec, Ontario and New Zealand. Each case is described based on key dimensions of Rainbow model of Valentijn and al (2013) with a focus on “meso level” integration. Meso level integration is represented by organizational and professional elements of the Rainbow Model, which are of particular interest in our nine case studies. Each of the three cases in Ontario and three in New Zealand are different and described separately. In Quebec, a local health services network model is presented across the three cases studied with variations in the way it is implemented. The three cases selected in the three jurisdictions under study were not chosen to be representative of wider practice within each country, but rather represent interesting and unique models of community-based primary healthcare integration. Similarities and variations in the integrated care models, context and dimension of integration offer insights regarding core component of integration of services, offering a foundational understanding of the cases on which future analysis will be based.